Analisis daya saing tenaga kerja pada front office dan housekeeping department di prama sanur beach hotel bali - Putra, Gede Ananda; Sulistyawati, Agung Sri; Sutaguna, I Nyoman Tri (Jurnal Kepariwisataan dan Hospitalitas, 2020)
Abstract The aim  of this research is to determine the competitiveness and strategy to increase the competitiveness aspect of Front Office and Housekeeping Department especially room attendant section at Prama Sanur Beach Hotel, based on MEA 2015 drives competition between all labors more increasing. This research also based on the Front Office staff largely had above 20 years of service and had age above 45 years . The located of this research was in Prama Sanur Beach Hotel, Cemara street, Sanur Village, Denpasar. The tecnique of collecting data were observation, interviews, documentation and questionare.The technique of sampling in this research used quota and incidental sampling. The kind of data are qualitative and quantitative data, while source of data are primary data and secondary data. This research used descriptive analysis, data reduction, likert scale analysis and SWOT Analysis Based on the results of this research, Guest Service Attendant has score 4,30 category very good, Concierge has score 4,11 category good, GuestRelation Officer has score 4,30 category very good, Telepon Operator has score 3,94 category good and the average score is 4,15 category good and be able to have improvement. Room Attendant has score 4,15 category good and be able to have improvement. Some main strategy in Front Office there are departemental training, section training, refreshment training, handling complaint training, internal trainer, and employes sertification. Strategy in Housekeeping Department there are   departemental training, handling guest complaint training, internal trainer, employes sertification, outing intern department program.   Keywords           : Competitiveness, Labor, Front Office Department, Housekeeping Department